Correlation between porosity and permeability of carbonate rock reservoirs. Issue 11 (3rd June 2017) - Chilingar, G.; Long, W.
ABSTRACT: It is critical to use proper definition of effective porosity, i.e., effective porosity as used in the USA minus the irreducible fluid saturation. Inasmuch as logs do not determine the irreducible fluid saturation, a lot of misinformation is spread around.